If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(n+5)=-2n+10
We move all terms to the left:
2(n+5)-(-2n+10)=0
We multiply parentheses
2n-(-2n+10)+10=0
We get rid of parentheses
2n+2n-10+10=0
We add all the numbers together, and all the variables
4n=0
n=0/4
n=0
| -144=8(v-10) | | 3x-164=136-12x | | 4n^2+8n+8=0 | | x=133.33 | | 30+3w=90 | | -71+x=-5x+61 | | F(-2)=8x+3 | | 30=3x+90 | | 10/5=n12 | | -52+x=48-3x | | 9x^2-27x=15 | | 4g+58.50=76.50 | | -137-x=-8x+38 | | -79-5x=-14x+65 | | -6x-88=-12x+68 | | (2x+4)+(5x-12)= | | 3(x+10)=20-7x | | 20x=176 | | 1/3-2/5x=-1/3x+4/5 | | 9-3x=6(x-3) | | 8x-21=6x+45 | | (√3-41)(7i)=0 | | r+1/5=32/15 | | x=-1000x+40 | | -5=h/ | | 0=-16t^2+260t-195 | | 5(2x+1)=3(x+4)-5, | | 31x+21=31x+21 | | 5(2x+1)=3(x+4)-5,x= | | 2x=14=60 | | 2y-84-240,y=162 | | (12x-4)=(6x+8) |